Students’ Self-Confidence and Its Impacts on Their Learning Process - Akbari, Omidullah; Sahibzada, Javed (American International Journal of Social Science Research, 2020)
The purpose of this study was to measure students’ self-confidence and finds its impacts on their learning process at Kandahar University. The study is descriptive in nature where quantitative questionnaire is used to collect data through stratified sampling from 1375 male and female students. The findings revealed only some of the students were low self-confident and most students were highly self-confident. In addition, students’ self-confidence effected their learning in areas of students’ participation, in seeking goal, developing interest in lessons, in decreasing students’ anxiety, they are being comfortable with their instructors and classmates and also in sharing their opinions related to lessons in class.